Riga, Latvijas Mākslas akadēmijas Mākslas vēstures institūts - Latvijas Mākslas Akadēmija (2011)
[Dt.:] Die Webseite bietet Informationen zu Forschungsthemen, Projekten, Veranstaltungen, Veröffentlichungen und Mitarbeitern des Kunsthistorischen Instituts der Lettischen Kunstakademie. - [Engl.:] The website offers information about research topics, projects, publications and staff members of the Institute of Art History of the Latvian Academy of Art.